Machinery & Parts Industry of Punjab - An Empirical Analysis of Growth and Productivity - Kumar, Gulshan (Prabandhan: Indian Journal of Management, 2011)
In the globalised business environment, no business can survive unless it is efficient and makes productive use of its resources. The small scale machinery&parts industry in Punjab has stood the test of time and has succeeded in meeting squarely, all the challenges posed during the pre-liberalisation and liberalisation period. The present study is an endeavour to investigate growth pattern and productivity trends of small scale machinery and parts industry of Punjab. The growth of industry has been measured in terms of four variables namely: number of units, fixed investment, employment and production. Yearly growth rates have been computed to glance at the year to- year fluctuations in growth and compound annual growth rates (CAGRs) have been worked out to find the impact of the policies of liberalized regime on growth of this industry. Productivity trends have been sketched in terms of capital intensity, capital output ratio and partial factor productivities. In order to comprehend the strengths and weaknesses of the industry, SWOT analysis has been conducted. The study observed that the policies of liberalization have enhanced capital investment and factor productivities, but resulted in sluggish growth in number of units and remarkable deceleration in the employment opportunities.